Heterogeneous response of the stock market to CO2 emissions in China - Li, Wenhui; Liu, Tianzi; Wei, Mengying (Frontiers in Energy Research, 2023)
CO2 emission has been a great challenge in China, especially in recent years. Meanwhile, the CO2 emissions allowance price cannot accurately reflect the CO2 emissions information in China because of the limited efficiency in China's carbon market. Accordingly, this study constructs a CO2 emissions index and provides an empirical investigation of the heterogeneous response of stock markets to CO2 emissions. With a quantile regression approach, we document that the effect of CO2 emissions on stock returns is significant in 2021, while it is insignificant in 2019 and 2020. In addition, its influence is more significant at the upper and low quantiles than at the median quantiles. Our findings indicate that investors and the government should pay more attention to carbon risk in the future and extreme market conditions.